Associated factors and quality of life in women with urinary incontinence in southern Peru, 2023 - Sologuren-García, Gema; Linares, Carmen L.; Flores, Jackeline R.; Escobar-Bermejo, Gloria; Sotelo-Gonzales, Soledad; Fagerstrom, Cristhel K. (Frontiers in Public Health, 2024)
BackgroundUrinary incontinence (UI), which can be classified as stress, urgency, or mixed, represents a public health problem that mainly affects adult women. This study aimed to determine the prevalence, association of sociodemographic and obstetric factors with the types of UI as well as the perceived impact on quality of life of women attending primary health facilities in the Tacna region from Peru.MethodsA quantitative, non-experimental, correlational, and cross-sectional study was conducted. Stratified sample. A total of 346 women aged 30 to 64 years were surveyed, applying two short version instruments: the Urinary Discomfort Inventory Questionnaire (UDI-6) and the Urinary Incontinence Impact Questionnaire (IIQ-7). Descriptive statistics, parameters of the multinomial logistic regression, with the B values, odds ratio (OR) and significance level (p < 0.05).ResultsThe prevalence of UI was 80.9%, with mixed UI being more frequent (48.8%). A significant association was found between the sociodemographic factor of educational level and type of UI (p = 0.004). Obstetric factors: higher frequency of mixed urinary incontinence (MUI) in vaginal delivery (30.6%) and newborns weighing 2,500–3,999 grams (35.5%). Additionally, an association between quality of life and type of urinary incontinence was observed, with a greater impact on those who had MUI (18.2%).ConclusionThere is a high prevalence of UI in women in the Tacna region, the sociodemographic associated is educational level. There is an association between quality of life and UI, with MUI being more frequent.